2010
DOI: 10.3329/jhpn.v28i3.5555
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Costs of Pregnancy- and Puerperiumrelated Care: Experience from a Hospital in a Low-income Country

Abstract: Calculation of costs of different medical and surgical services has numerous uses, which include monitoring the performance of service-delivery, setting the efficiency target, benchmarking of services across all sectors, considering investment decisions, commissioning to meet health needs, and negotiating revised levels of funding. The role of private-sector healthcare facilities has been increasing rapidly over the last decade. Despite the overall improvement in the public and private healthcare sectors in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…While, due to the nature of this survey, we were not able to separate the components of OOP, earlier studies in this context have observed that along with direct medical cost, travel, food, lodging, hiring of an “aya,” and even tip‐giving were all major components of child delivery costs . A previous hospital‐based study in Bangladesh reported that the cost of normal delivery and C‐section at public facilities was approximately US$ 44 and US$ 90, at the price level of 2007 . A couple of community‐based studies in this context observed that, for a normal delivery, households spent anywhere from US$ 24 up to US$ 32, while in C‐section, the OOP was raised from US$ 118 to US$ 230 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…While, due to the nature of this survey, we were not able to separate the components of OOP, earlier studies in this context have observed that along with direct medical cost, travel, food, lodging, hiring of an “aya,” and even tip‐giving were all major components of child delivery costs . A previous hospital‐based study in Bangladesh reported that the cost of normal delivery and C‐section at public facilities was approximately US$ 44 and US$ 90, at the price level of 2007 . A couple of community‐based studies in this context observed that, for a normal delivery, households spent anywhere from US$ 24 up to US$ 32, while in C‐section, the OOP was raised from US$ 118 to US$ 230 .…”
Section: Discussionmentioning
confidence: 86%
“…The lower cost in public facilities reflect that these public facilities are highly subsidized by the government of Bangladesh and occasionally receive national and international donations for the purchasing of goods . Thus, the financial cost is often shared among the households and the hospitals, whereas in the cases of private facilities, all expenditure (including profits) have to be raised from the households.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In India, hospital services are increasingly used both by those paying out of pocket as well as by beneficiaries of the government-supported insurance scheme Rashtriya Swasthya Bima Yojona (RSBY), which covers the cost of both inpatient and surgical services. RSBY, the country's largest government-backed hospital-based health insurance scheme, covers 32.4 million poor families, provides rupees 500 per day for inpatient stay, and covers more than 725 surgical procedures.…”
Section: Key Messagesmentioning
confidence: 99%
“…Conducting “unnecessary” CS for women who do not really need this intervention could put a strain on existing and limited healthcare resources [ 14 ] as well as family financial security [ 15 , 16 ] and become a barrier to achieving universal and geographically equitable coverage with CS where this is medically indicated [ 4 ].…”
Section: Introductionmentioning
confidence: 99%